The effect of a carbohydrate loading on running performance during a 25-km treadmill time trial by level of aerobic capacity in athletes - Sullo, A.; Monda, M.; Brizzi, G.; Meninno, V.; Papa, A.; Lombardi, P.; Fabbri, B. (European Review for Medical and Pharmacological Sciences, 1998)
The aim of the present study was to examine the influence of a high carbohydrate diet and the level of aerobic capacity on running performance during a 25-km treadmill time trial. The study used a 2*2 design with the factors being training and diet composition. We divided the athletes in 4 groups: 1. Trained athletes with carbohydrate loading (CHO1); 2. Trained athletes without carbohydrate loading (C1); 3. Untrained athletes with carbohydrate loading (CHO2); 4. Untrained athletes without carbohydrate loading (C2). The carbohydrate loading was effected with confectionery. Performance time, running speed, blood glucose and blood lactate concentrations were evaluated during two 25-km treadmill time trial (trial 1 and trial 2) separated by 7 days in which two groups (CHO1 and CHO2) had a carbohydrate loading. The results showed that the athletes with lower level of aerobic capacity had better performance time after carbohydrate loading. They ran faster and had a higher glucose and lactate concentrations in the last 5 km during trial 2. There were no significant differences in the other groups. In conclusion, we can assert that dietary carbohydrate loading can improve running performance and that confectionery can be used as an effective means of supplementing the normal carbohydrate intake in preparation for endurance competitions. But the improvement depends on some factors such as the distance and the level of aerobic capacity.